Carbon and energy prices : surfing the wavelets of California - Sousa, Rita (2014)
Carbon price is a key variable in management and risk decisions in activities related to the burning of fossil fuels. Using innovative multivariate wavelet analysis, we study the link between carbon prices and primary and final energy prices in the time and frequency dimensions, particularly in longer cycles (4 ∼ 8 and 8 ∼ 20 months). We show a tight relation between carbon and electricity prices, co-moving together in one-year cycles, with electricity slightly leading, in opposition with previous results obtained for Europe. Thus, an over-allocation of allowances to the power generating sector is suggested. We also find indication of an out-of-phase relation between carbon and oil prices, with oil leading, and expect this relation to intensify when including fuel distributors in the CA market. Finally, and contrary to EU ETS previous results, we do not find a significant relation between carbon and economic activity. In conclusion, although our results are not as significant as the ones previously obtained by other authors, for Europe, they show that the variables are related in the longer term, which supports the development of emissions trading in the post-2020.